Points, Points, and More Points: High School Grade Inflation and Deflation when Homework and Employability Scores are Incorporated (Journal of School Administration Research and Development, 2021)
With a strong movement of schools starting to use standards-based grading practices, one of the aims of this study was to learn if traditional grading practices communicate grades that are accurate based on the students’ learning of the course objectives. The purpose of this study was to determine the extent to which employability and homework scores within a traditional points- and percentages-weighted grading model inflates or deflates grades. This study analyzed 795 students’ semester math grades at an urban high school to see if, and to what extent, students’ grades were inflated or deflated due to including homework and employability scores in the grade. Final grades, which included homework and employability points, were compared to each student’s overall summative assessment scores to determine grade inflation or deflation. The study also analyzed how changing grading practices to eliminate homework and employability points would impact the number of students that ultimately passed or failed the course. Results of this study indicated 336 (43.2%) students had their grades inflated or deflated by 5% or more and 97 (12.6%) students had their grades inflated or deflated by 10% or more, which is equivalent to moving up or down a full letter grade. School leaders should consider separately communicating academic and non-academic factors to minimize grade inflation/deflation in order to make decisions based upon grades more justifiable.